Noradrenergic symptom cluster in depression - Montgomery S (Dove Medical Press, 2011)
Stuart Montgomery1, Mike Briley21Imperial College School of Medicine, London, UK; 2NeuroBiz Consulting and Communication, Castres, FranceDepression is characterized by a wide range of diverse symptoms, the severity of which can be quantified by various depression rating scales, such as the Montgomery Asberg Depression Rating Scale. Analyses of the individual items of this scale in patients treated with the selective serotonin reuptake inhibitors (SSRIs) have shown that not all items respond equally or with the same time of onset of improvement (Table 1).1,2 The items which respond less well or more slowly with SSRIs include lassitude, loss of energy, retardation of thoughts or actions, as well as concentration difficulties and loss of alertness. The loss of interest or pleasure that depressed patients experience (anhedonia) also responds poorly to SSRIs, and patients often complain of emotional indifference or blunting. Certain sleep difficulties are sometimes worsened by SSRIs. Appetite loss can be aggravated by certain SSRIs, an effect which can be made worse by nausea at the beginning of treatment.